Enhancing Students’ Reading and Listening Skills by Using Social Media Language Learning (SMLL) Approach through Features on Instagram Verified Accounts - Nurianti Sitorus; Ince Dian Aprilyani Azir (Universitas Cokroaminoto Palopo, 2021)
The utilization of social media is not limited to get entertained but it is now used to support the online learning process. Instagram, one of the social media applications, provides its users with verified accounts that are authentic and notable. This allows English learners to get the supporting materials to study reading and listening. Moreover, the features in Instagram are suitable to present the students with authentic materials in English from natives. This study aims to find out whether using materials taken from Instagram verified accounts enhance students’ skills in reading and listening to English. Social Media Language Learning (SMLL) is used as the approach to teaching the students several skills they might need for the international test. An experimental study method is applied while the data collection uses both quantitative and qualitative methods. Pretest and posttest are administered to perceive the students’ academic progress whereas interviews are organized to collect certain students’ opinions about this study. The participants of this study are 30 vocational learners in the fourth semester major in Graphic Design (Multimedia Concentration) at Polimedia PSDKU Medan. Following the evaluation of the students’ scores after each assessment and interviews after the training; the results reveal students’ improvement academically. As the findings indicate that social media language learning by using Instagram verified account enhances students’ ability in reading and listening and adequately supports creative and efficient learning.